My year inside radical Islam a memoir - Gartenstein-Ross, Daveed 1976- (Jeremy P. Tarcher/Penguin, 2007)
This memoir of first a spiritual and then a political seduction shows how a good faith can be distorted and a decent soul can be seduced away from its principles. Raised in liberal Ashland, Oregon, by parents who were Jewish by birth but dismissive of dogma, Gartenstein-Ross yearned for a religion that would suit all his ideals. At college in the late nineties he met a charismatic Muslim student who grounded his political activism with thoughtful religious conviction. Gartenstein-Ross reflects on his experience of converting to Islam--a process that began with a desire to connect with both a religious community and a spiritual practice, and eventually led him to sympathize with the most extreme interpretations of the faith. Gartenstein-Ross is now an attorney and a full-time counterterrorism consultant.